The ASEAN Way towards Piracy Challenge - Ikaningtyas, Ikaningtyas; Ruslijan, Patricia Audrey (Indonesian Journal of International Law, 2012)
Piracy is a universal crime that needs to be combated by all nations. International efforts have been done for many years in order to suppress growth of piracy for international maritime security, which resulted in provisions concerning piracy within United Nations Convention on the Law of the Sea. It refers piracy as a crime taking place on high seas. In addition, International Maritime Organization also attempts to widen the definition of piracy. Even so, tackling piracy requires more than just a commitment of international community to define the term. Efforts must also be conducted by regional community to make them more effective, especially with their national legal instrument. Association of Southeast Asian Nations (ASEAN) as the regional organization in Southeast Asia region has sought to better cooperation among the members bringing the six behavioral principles laid in Treaty of Amity and Cooperation 1976 and also ASEAN Charter 2007 for the purpose of eliminating piracy within their region. Unfortunately, piracy is manifestly not easy to be eradicated in reality. This paper tries to identify and analyze the challenges that underlie ASEAN efforts to solve the piracy problem within the region